Investigating the Mechanism of Ion Concentration Polarization Within Nanofluidic Hydrogel Membranes: Experiment and Simulation - Hiba Aljayyousi; Jongmin Kim; Serdal Kirmizialtin; Yong‐Ak Song (Advanced Materials Interfaces)
Abstract Ion concentration polarization (ICP) is an electrokinetic phenomenon observed near ion‐selective membranes in micro‐nanofluidic systems, affecting ion transport and localization. This process is essential for biosensing, desalination, energy storage, and electrochemical devices. This study combines experimental techniques and all‐atom molecular dynamics (MD) simulations to investigate the mechanisms underlying ICP. Electrostatic potential profiles across the nanochannel are analyzed, examining the effects of ionic strength, electric field strength, and membrane surface charge density on RNA localization and ion trapping. Simulations revealed a strong dependence of RNA localization on ionic strength. Cations localized by the electric field induced ion correlations, amplified by hydrostatic pressure gradients that led to vortex formation and biomolecule localization. Intermediate ionic strengths most effectively induced ICP. This study provides atomic‐level insights into ICP mechanisms, advancing understanding of this phenomenon and guiding the design of next‐generation ion‐selective membranes.